Research of a computer model of a synchronous hydroelectric generator - Stets, Sergiy; Stets, Andriy (Моделювання, керування та інформаційні технології, 2019)
The proposed computer model allows us to investigate the operation of the generator in normal and emergency modes, under dedicated load, or as part of a power system. The model allows to obtain graphs of instantaneous values ​​of currents, voltages, generator speed, active power.